The Effects of Language and Semantic Repetition on the Enactment Effect of Action Memory - Zhang, Xinyuan; Zuber, Sascha (Frontiers in Psychology, 2020)
Humans exhibit enhanced memory performance when information is encoded by physically enacting it, as opposed to passively reading or hearing the same information; an effect referred to as “enactment effect.” The present study explored the effects of language (native vs. non-native) and semantic repetition (repeated vs. non-repeated) on the enactment effect in action memory. Forty-eight subjects learned action phrases either by enacting or by reading the items. Results showed (i) better memory for enacted phrases, (ii) better memory for non-native repeated phrases that were only read, (iii) no difference in memory between repeated and non-repeated phrases that were enacted, and (iv) that semantic repetition affected memory of phrases that were read but not of those that were enacted. Partly in line with the multimodal theory, findings support that enacting action phrases can enhance item-specific processing and that this is insensitive to cognitive strategies like semantic repetition.